Implications of Islamic Fintech in the Macroeconomy: A Comparative Study of Indonesia and Malaysia - Nurul Fajriatussaadah; Wahab Zaenuri; Ali Murtadho (El-Fata: Journal of Sharia Economics and Islamic Education, 2025)
This study examines the role of Islamic fintech in driving macroeconomic growth through a case study of Indonesia and Malaysia. The key issue addressed is how Islamic fintech strengthens financial inclusion, reduces economic inequality, and enhances economic stability through Sharia-compliant financing. The research aims to analyze the impact of Islamic fintech on macroeconomic indicators, such as Gross Domestic Product (GDP) growth and unemployment reduction, while comparing its implementation in both countries. Using a qualitative approach with a case study method, primary and secondary data were collected through online documentation and literature analysis. The findings reveal that Islamic fintech significantly supports MSMEs, enhances financial inclusion, and improves resource allocation efficiency. Malaysia excels in its Islamic financial ecosystem, while Indonesia shows substantial potential due to its large Muslim population. This research contributes novelty by exploring the macroeconomic impacts of Islamic fintech and providing strategic recommendations for its future development.